1999
DOI: 10.1103/physrevlett.83.5374
|View full text |Cite
|
Sign up to set email alerts
|

Optical Demonstration of a Crystal Band Structure Formation

Abstract: The optical modes of chains of coupled micron sized semiconductor cavities have been studied using photoluminescence spectroscopy and detailed calculations. With an increasing number of cavities, the chains exhibit photon band gaps at several Brillouin zone boundaries. The sizes of the band gaps are shown to depend on the coupling between the microcavities and also on the order of the Brillouin zone involved. PACS numbers: 78.55.Cr, 42.70.Qs Systems which exhibit photon band gaps analogous to the band gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…This is analogous to the transition from atomic-like discrete states to the continuous spectrum in solid-state physics. Recently, Bayer et al observed formation of a photonic band due to coupling between the optical molecules [18].In this communication, we demonstrate the guiding of light through localized coupled optical cavity modes in 1D PBG structures which are fabricated from siliconoxide/silicon-nitride (SiO 2 /Si 3 N 4 ) pairs with λ/2 SiO 2 cavity layers. It is observed that nearly 100% transmission can be achieved throughout the waveguiding band.…”
mentioning
confidence: 95%
“…This is analogous to the transition from atomic-like discrete states to the continuous spectrum in solid-state physics. Recently, Bayer et al observed formation of a photonic band due to coupling between the optical molecules [18].In this communication, we demonstrate the guiding of light through localized coupled optical cavity modes in 1D PBG structures which are fabricated from siliconoxide/silicon-nitride (SiO 2 /Si 3 N 4 ) pairs with λ/2 SiO 2 cavity layers. It is observed that nearly 100% transmission can be achieved throughout the waveguiding band.…”
mentioning
confidence: 95%
“…The polaritons resulting from the strong coupling of these photon modes with the quantum well exciton will also display a mixed spectrum containing both confined and extended states. In addition to an easier fabrication approach, this kind of structure features a considerable difference with respect to micropillars, 18,19,22 where photon confinement is obtained by etching the whole cavity body, thus resulting exclusively in confined modes.…”
Section: Patterned Mesas In Microcavitiesmentioning
confidence: 99%
“…Moreover, the discrete spectrum is the key feature 14 to overcome the effect of quantum fluctuations that dominate a two-dimensional interacting Bose gas, and opens the way to the observation of collective many-body effects. [15][16][17] Attempts to produce spatially confined polariton states, in the past, have been made by etching micropillars 18,19 of a few m in diameter from an initially planar MC. [20][21][22][23] These structures have in general proved able of producing lateral confinement of polariton modes.…”
Section: Introductionmentioning
confidence: 99%
“…The optical modes of a linear array of GaAs cavities with InGaAs quantum wells as the optically active material, were measured by angle-resolved photoluminescence spectroscopy, demonstrating the creation of a continuum of mode energy distributions from a discrete family as the number of resonators increases [23]. Narrowing the width of the GaAs channels connecting the cavities resulted in a larger bandgap at the Brillouin zone boundaries, in accordance with the increased modulation of the dielectric function along the waveguide.…”
Section: Experimental Progress and Applications Of Crowsmentioning
confidence: 88%
“…The formation, when the number of resonators is increased, of a continuous dispersion relationship such as (5) from a discrete spectrum by reduction of the mode energy splitting of the individual resonators has been discussed elsewhere [22], [23]. In the limit of nearest-neighbor coupling, as applicable to waveguides formed by coupling high-Q resonators, the parameter in (3) is given in terms of the spatial variation of the dielectric constant by .…”
Section: Crow Waveguide Modesmentioning
confidence: 99%